Susceptibility of Helicoverpa gelotopoeon (Lepidoptera: Noctuidae) to generalist AcMNPV and comparative pathogenicity of a specific nucleopolyhedrovirus - Arneodo Larochette, Joel Demian (2025)
Helicoverpa gelotopoeon Dyar (Lepidoptera: Noctuidae) is a major agricultural pest in southern South America. Autographa californica multiple nucleopolyhedrovirus (AcMNPV) is a generalist baculovirus that was proven to be highly pathogenic to several lepidopteran species, some of which co-occur in time and space with H. gelotopoeon. Here, the infectivity of AcMNPV to H. gelotopoeon larvae was assessed through bioassays, molecular methods and microscopy. AcMNPV infection in H. gelotopoeon did occur, but the speed of kill was extremely slow. For comparative purposes, bioassays using specific Helicoverpa gelotopoeon single nucleopolyhedrovirus (HegeSNPV) showed a relatively fast lethal effect. Both viruses had similar tissue tropism, however symptom development differed: AcMNPV-infected larvae retained an intact integument, whereas HegeSNPV caused tissue liquefaction. HegeSNPV, rather than AcMNPV, could serve as a biocontrol agent against this pest.